Harmoni Manusia dan Alam dalam Antologi Puisi Karya D. Zawawi Imron; Relevansi terhadap Pembelajaran Bahasa Indonesia - Moh Tabarok; Mega Miranda; Qurratul Aini; Ari Ambarwati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the Harmony of Man and Nature in poetry by D. Zawawi Imron and its relevance to Indonesian language learning. Using an ecocritical approach, this study analyzes the elements of nature presented in Imron's poems, especially in relation to the interaction between humans and their environment. This study also explores how these poems can be used as learning media that teach environmental values ​​and shape ecological awareness in students. Descriptive qualitative methods are used to reveal the ecological themes raised in these poems, as well as their implications for Indonesian language learning, especially in the material of poetry appreciation and character education. The results of the study show that D. Zawawi Imron's poems not only express the beauty of nature, but also describe environmental damage due to irresponsible human behavior. This ecological representation is relevant in learning because it provides educational values ​​that encourage students to care more about their surroundings. Thus, poetry as a literary work plays an important role in building environmental awareness and can be integrated into Indonesian language teaching materials at various levels of education.